The role of Gardnerella vaginalis, Autopobium vaginae and Mobiloncus spp in preterm delivery: A case-control study - Sedigheh Livani; Sepideh Bakhshandeh Nosrat; Mahdiheh Naghavi Alhosseini; Amene Sadat Sheykholeslami; Mohammad Ali Vakili; Ezzat Allah Ghaemi (Mashhad University of Medical Sciences, 2023)
Introduction: Preterm delivery is one of the leading causes of death in infants and children under 5 years of age. The causes of preterm delivery have not been properly identified, but some causes include infections such as bacterial vaginosis, which are very common among pregnant women. The present study was performed with aim to determine the role of bacteria associated with bacterial vaginosis in causing preterm delivery. Methods: This case-control study was conducted in 2014-2015 on 100 women with term delivery and 100 women with preterm delivery in Shaheed Sayyad Shirazi hospital in Gorgan. DNA was extracted from vaginal samples and PCR was performed using specific primers for Atopobium vaginae, Gardnerella vaginalis and Mobiloncus spp. The data were analyzed using SPSS software (version 16) and Chi-square test and logistic regression. P<0.05 was considered statistically significant. Results: Frequency of Gardnerella, Atopobium and Mobiluncus in term delivery were 86%, 15% and 25%, respectively and in preterm delivery were 74%, 14%, and 45%, respectively.  The distribution of Mobiloncus in the two groups of preterm and term delivery had a statistically significant relationship (P=0.003). The odds ratio (OR) of preterm delivery in women who were positive for Mobiloncus was 2.46 times (95% confidence interval 1.35-4.47) compared to those who were negative for Mobiloncus. Conclusion: According to the findings of this study, the odds ratio of preterm delivery was significantly increased with the presence of Mobiloncus in the vagina. It is better to consider the methods to quickly detect this bacterium and thus prevent preterm delivery.